2018
DOI: 10.1021/acsnano.8b07104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrostatic Pressure on the Surface Plasmon Resonance of Gold Nanocrystals

Abstract: The surface plasmon resonances of gold nanospheres and nanorods have been measured as a function of hydrostatic pressure up to 17 GPa in methanol−ethanol 4:1 solvent and up to 10 GPa in paraffin. Both the sphere resonance and the longitudinal rod resonance exhibit redshifts, whereas the transverse rod mode shows an extremely weak redshift or blueshift depending on the nanorod aspect ratio. Solidification of the solvent around 11 GPa causes some aggregation of the particles, readily identified through broadenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 24 publications
3
47
1
Order By: Relevance
“…In particular, the surface plasmon spectroscopy-based n(P) data are very similar to those obtained by combining Brillouin spectroscopy and sound velocity measurements under high-pressure conditions. Interestingly, the LSPR pressure shifts of aqueous AuNR dispersions are well described by a modified Mie-Gans model, in agreement with previous findings for AuNR dispersions in alcohol[4]. We also show that the analysis of the two main competing mechanisms responsible for LSPR -the compression of conduction electrons in the metal causes a blueshift while an increase in solvent density under pressure leads to a redshiftenables us to decouple both effects, thereby providing a direct approach to extract the variation of the refractive index of water n(P) from the LSPR pressure shift across the three investigated water phases: liquid, ice VI and ice VII.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…In particular, the surface plasmon spectroscopy-based n(P) data are very similar to those obtained by combining Brillouin spectroscopy and sound velocity measurements under high-pressure conditions. Interestingly, the LSPR pressure shifts of aqueous AuNR dispersions are well described by a modified Mie-Gans model, in agreement with previous findings for AuNR dispersions in alcohol[4]. We also show that the analysis of the two main competing mechanisms responsible for LSPR -the compression of conduction electrons in the metal causes a blueshift while an increase in solvent density under pressure leads to a redshiftenables us to decouple both effects, thereby providing a direct approach to extract the variation of the refractive index of water n(P) from the LSPR pressure shift across the three investigated water phases: liquid, ice VI and ice VII.…”
supporting
confidence: 91%
“…is the nanorod depolarization or shape factor, = 2 is the dielectric function of the non-absorbing medium, which also yields a refractive index, , while in Eq.2 is a renormalization constant. The change in particle volume The Journal of Physical Chemistry Letters analysis of extinction spectra of gold nanocrystal colloids in ethanol-methanol mixtures over a range of hydrostatic pressures [4]. We found that the bulk modulus of gold for an AuNR of 0 = 190 GPa is significantly higher than that for bulk gold metal, 0 = 167 GPa [23].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Plasmonic nanoparticles (PNPs) have been the focus of research in fields as diverse as chemical and biological sensing and solar energy harvesting due to the unique optical properties originating from surface plasmon resonance (SPR). [ 1–8 ] PNPs have many desirable properties, including good conductivity, easy modification, low toxicity, and excellent biocompatibility. Furthermore, single PNPs are extremely sensitive to chemical composition, morphology, surface chemistry, and the localized surrounding medium.…”
Section: Introductionmentioning
confidence: 99%